Effect Of UV-Assisted Titanium Dioxide (TiO2) Photocatalysis on Viable Airborne Bacteria and Fungi in The Seasoning Powder Industry - Cakrawati, Dewi; Aprilianto, Kevin; Faridah, Chintya Nur; Utami, Kiki Diyah Ayu (Journal of Agri-Food Science and Technology, 2023)
Titanium dioxide (TiO2) has been known to have anti-microbial activity against fungi, bacteria, and viruses. The application of TiO2 in the membrane attached to the air conditioner was expected to minimize airborne microorganisms. This study contribution to investigate the efficacy of UV-assisted TiO2 photocatalysis in controlling airborne microorganisms in the seasoning powder industry. TiO2 was coated to the non-woven membrane and attached with a UV lamp inside the air conditioner. When the AC was on, the Ti3+ was released into the air. Enumeration of airborne microorganisms was conducted by opening the agar plates for 15 min at several food processing facilities, followed by incubating agar plates for 72 hours at 30 °C. The result shows dry processing facility had the highest number of initial airborne bacteria while the wet production facility had the highest number of initial airborne fungi. Interestingly, the number of airborne microorganisms fluctuated in the packaging facility related to the number of people going inside and outside. On the contrary, the number of airborne microorganisms was deficient in empty rooms, which indicated that the number of airborne microorganisms might be related to people and products. Overall, airborne microorganisms were reduced after 60 min of irradiation. Therefore, it is recommended to irradiate the facilities for 60 min before production start. SEM images and EDAX analysis results show TiO2 was detected after 160 h. However, it was recommended to change the TiO2 membrane after one month. This research was expected to contribute to controlling airborne microorganisms during food production in food processing facilities.